2007
DOI: 10.1159/000100868
|View full text |Cite
|
Sign up to set email alerts
|

Penile Metastasis from a T1b Prostate Carcinoma

Abstract: Penile metastasis from incidental prostate carcinoma has not been described to date. Case Report: The case of a 72-year-old man affected by penile metastasis from incidental prostate carcinoma is described. In March 1998, the patient underwent prostate surgery for lower urinary tract symptoms related to benign prostatic obstruction. Histological examination revealed an incidental adenocarcinoma of the prostate. The pre-operative prostate-specific antigen (PSA) value was 3.6 ng/ml. A prostate biopsy in the peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
0
3
0
1
Order By: Relevance
“…Das Prostatakarzinom als häufigster Tumor des Mannes metastasiert nur in weniger als 0,3 % der Fälle in Penis oder Hoden [5]. In den beschriebenen Fällen ist meist eine antiandrogene Therapie des Prostatakarzinoms vorausgegangen [6,7]. Es wird vermutet, dass hierdurch bestimmte Subtypen selektioniert werden.…”
Section: Aktuelle Befunde Und Weiterführende Diagnostikunclassified
“…Das Prostatakarzinom als häufigster Tumor des Mannes metastasiert nur in weniger als 0,3 % der Fälle in Penis oder Hoden [5]. In den beschriebenen Fällen ist meist eine antiandrogene Therapie des Prostatakarzinoms vorausgegangen [6,7]. Es wird vermutet, dass hierdurch bestimmte Subtypen selektioniert werden.…”
Section: Aktuelle Befunde Und Weiterführende Diagnostikunclassified
“…Rare penile cancers include melanoma, basal cell carcinoma, sarcomas, fibrous histiocytoma and secondary carcinomas. 1,4,5 Squamous cell cancer usually starts on glans or coronal sulcus as a nodule, foul smelly ulcer or cauliflower like mass, which invades corpora cavernosa as it progresses sparing the urethra until late in the course of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…The most common primary malignancies with penile metastases are urogenital cancers (69%) followed by cancers from gastrointestinal origin (19%) [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 ]. The clinical manifestations are heterogeneous, ranging from penile nodules to masses, with or without ulceration, obstructive or irritative urinary symptoms, hematuria or priapism.…”
Section: Introductionmentioning
confidence: 99%
“…The clinical manifestations are heterogeneous, ranging from penile nodules to masses, with or without ulceration, obstructive or irritative urinary symptoms, hematuria or priapism. It has been suggested that the occurrence of priapism as a consequence of malignancy may be a prognostic factor to take into account [ 2 , 3 , 5 , 10 , 12 ].…”
Section: Introductionmentioning
confidence: 99%